Five types on perception of global warming in Japanese - Kosugi, Motoko; Baba, Kenshi (Frontiers in Climate, 2023)
Introduction: The study seeks to examine Japanese people's perceptions and attitudes toward climate change by segmenting and characterizing respondents using online survey data from 2017 and 2020. Methods: The survey administered in 2017 had 2,997 respondents and the survey in 2020, 1,100 respondents. Five segments were identified based on aspects of people's understanding of global warming, their attitudes toward taking countermeasures, and analyses of the characteristics and changes in the segment composition. Results: The groups identified were the "Alarmed," who have a strong sense of urgency and undertake proactive measures; the "Indifferent," who have limited interest and no clear opinion; the "Affirmative," who tend to agree with all questions regardless of their content; and the "Skeptic," who tend to suspect global warming. provide negative responses to contradictory questions. The 2017 survey also yielded a segment called "Dismissive 2017," and in the 2020 survey, a new segment called "Cautious 2020" was identified. People with unclear perceptions about climate change accounted for about 50% of respondents in both surveys. Conclusion: The findings suggest that in communicating with the public regarding the implementation of countermeasures, it is necessary to consider the differences in awareness, knowledge, and perception of the effects of global warming among various segments of the population.